2023
DOI: 10.1021/acsami.3c09363
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Anchoring of Graphitic Carbon Nitride on MnO2 Nanoarchitectures for Oxygen Evolution Electrocatalysis

Mattia Benedet,
Andrea Gallo,
Chiara Maccato
et al.

Abstract: The design and fabrication of eco-friendly and costeffective (photo)electrocatalysts for the oxygen evolution reaction (OER) is a key research goal for a proper management of water splitting to address the global energy crisis. In this work, we focus on the preparation of supported MnO 2 /graphitic carbon nitride (g-CN) OER (photo)electrocatalysts by means of a novel preparation strategy. The proposed route consists of the plasma enhancedchemical vapor deposition (PE-CVD) of MnO 2 nanoarchitectures on porous N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…1,8,16,18,28 In line with these results, N 1s components (Fig. 2d) were related to bi-coordinated nitrogen (CN–C; VII, BE = 398.7 eV), 4,8,24,28 tertiary N–(C) 3 atoms (VIII, BE = 399.9 eV), 1,8,24,26,28 and –NH x groups (IX, BE = 401.1 eV). 3,16,28,45…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…1,8,16,18,28 In line with these results, N 1s components (Fig. 2d) were related to bi-coordinated nitrogen (CN–C; VII, BE = 398.7 eV), 4,8,24,28 tertiary N–(C) 3 atoms (VIII, BE = 399.9 eV), 1,8,24,26,28 and –NH x groups (IX, BE = 401.1 eV). 3,16,28,45…”
Section: Resultssupporting
confidence: 78%
“…2c), beside the adventitious carbon band (IV, BE = 284.8 eV), 3,9,16,25,28 presented a component at ≈286.1 eV (V) due to both C–O bonds and −C−NH x moieties ( x = 1,2) on gCN heptazine ring edges. 3,4,17,24,44 Finally, signal VI at BE ≈ 288.1 eV was attributed to N–CN carbon atoms in gCN. 1,8,16,18,28 In line with these results, N 1s components (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… In addition, the peaks at 451.9 and 444.4 eV can be attributed to In 3+ 3d 3/2 and 3d 5/2 , respectively, and the S 2p spectrum can be fitted to two peaks at 162.5 and 161.4 eV (Figure e,f), which are assigned to S 2– 2p 1/2 and 2p 3/2 , respectively . After forming a p – n heterojunction in 10 wt % CIS@TCOF, it is noteworthy that the binding energies of Cu 2p, In 3d, and S 2p show a negative shift, while the binding energy of N 1s shows a positive shift, compared with those in pure CIS and TCOF, which is in accordance with the general rule for heterojunction-type photocatalysts. To determine the direction of the electron transfer during photocatalysis, the in situ irradiated XPS of 10 wt % CIS@TCOF was carried out under light irradiation. Compared with 10 wt % CIS@TCOF in darkness, it can be observed that the C 1s and imine-N 1s peaks of TCOF markedly shift to the low binding energy (Figure b,c), while the Cu 2p, In 3d, and S 2p peaks of the 10 wt % CIS@TCOF composite under light irradiation obviously move toward the high binding energy (Figure d–f), implying that the photogenerated electrons transfer from CIS to TCOF under light irradiation. , Therefore, these XPS results provide important evidence of the photogenerated charge carrier transfer pathway across the CIS@TCOF heterojunction interface.…”
Section: Resultsmentioning
confidence: 89%